Temporal analysis of reported cases of tuberculosis and of tuberculosis-HIV co-infection in Brazil between 2002 and 2012 - Renato Simões Gaspar; Natália Nunes; Marina Nunes; Vandilson Pinheiro Rodrigues (Jornal Brasileiro de Pneumologia)
ABSTRACT Objective: To investigate the reported cases of tuberculosis and of tuberculosis-HIV co-infection in Brazil between 2002 and 2012. Methods: This was an observational study based on secondary time series data collected from the Brazilian Case Registry Database for the 2002-2012 period. The incidence of tuberculosis was stratified by gender, age group, geographical region, and outcome, as was that of tuberculosis-HIV co-infection. Results: Nationally, the incidence of tuberculosis declined by 18%, whereas that of tuberculosis-HIV co-infection increased by 3.8%. There was an overall decrease in the incidence of tuberculosis, despite a significant increase in that of tuberculosis-HIV co-infection in women. The incidence of tuberculosis decreased only in the 0- to 9-year age bracket, remaining stable or increasing in the other age groups. The incidence of tuberculosis-HIV co-infection increased by 209% in the ≥ 60-year age bracket. The incidence of tuberculosis decreased in all geographical regions except the south, whereas that of tuberculosis-HIV co-infection increased by over 150% in the north and northeast. Regarding the outcomes, patients with tuberculosis-HIV co-infection, in comparison with patients infected with tuberculosis only, had a 48% lower chance of cure, a 50% greater risk of treatment nonadherence, and a 94% greater risk of death from tuberculosis. Conclusions: Our study shows that tuberculosis continues to be a relevant public health issue in Brazil, because the goals for the control and cure of the disease have yet to be achieved. In addition, the sharp increase in the incidence of tuberculosis-HIV co-infection in women, in the elderly, and in the northern/northeastern region reveals that the population of HIV-infected individuals is rapidly becoming more female, older, and more impoverished.